2018
DOI: 10.1167/tvst.7.5.19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical CNV and Choriocapillaris Nonperfusion in Fellow Eyes of Unilateral Exudative AMD on OCT Angiography

Abstract: PurposeTo determine the prevalence of subclinical choroidal neovascularization (CNV) in fellow eyes of patients with unilateral exudative age-related macular degeneration (AMD) using optical coherence tomography angiography (OCTA) and to quantify choriocapillaris nonperfusion adjacent to CNV.MethodsWe retrospectively reviewed all patients with AMD who underwent OCTA and identified eyes with unilateral exudative AMD. We determined the presence of subclinical CNV on custom en face macular slabs of the outer reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 37 publications
3
35
2
Order By: Relevance
“…Imaging modalities that can identify the conversion of an early stage of AMD to nAMD are CFP, OCT, fluorescein angiography (FAG), indocyanine green angiography (ICGA) and OCT‐angiography (OCTA). Whereas CFP, OCT, and FAG can identify exudative nAMD by fluid leakage and haemorrhaging, in some cases a CNV can already be visualised before exudation occurs using ICGA and OCTA imaging …”
Section: Introductionmentioning
confidence: 99%
“…Imaging modalities that can identify the conversion of an early stage of AMD to nAMD are CFP, OCT, fluorescein angiography (FAG), indocyanine green angiography (ICGA) and OCT‐angiography (OCTA). Whereas CFP, OCT, and FAG can identify exudative nAMD by fluid leakage and haemorrhaging, in some cases a CNV can already be visualised before exudation occurs using ICGA and OCTA imaging …”
Section: Introductionmentioning
confidence: 99%
“…Despite various rates of bilateral presentation [3], many studies have identified asymptomatic lesions in fellow eyes of both PCV and nAMD patients. For example, nonexudative neovascularization of the fellow eye was found to be associated with pachychoroid pigment epitheliopathy in PCV and nAMD patients [7], and an increased trend of choriocapillaris (CC) nonperfusion was detected in the fellow eyes of nAMD using OCTA [8]. Additionally, retinal pigmented epithelium (RPE) and outer retinal abnormalities were observed in 84% of a cohort of unilateral PCV patients, and CNV formation was observed more if these abnormalities were accompanied with pachyvessels [9].…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Several studies have investigated FD of the CC in the perilesional low-flow dark halo (DH) surrounding MNV using en face OCTA analysis. 1 , 16 19 …”
mentioning
confidence: 99%